Inventory and immobile cultural heritage management in the Portuguese General Directorate for the Cultural Heritage - Gomes, Ana Sofia; Leite, Sílvia; Neto, Filipa; Oliveira, Catarina; Bragança, Filipa (DISEGNARECON, 2012)
The Directorate General for Cultural Heritage (DGPC) is responsible for managing the inventory of listed heritage, heritage awaiting listing, as well as archaeological heritage in mainland Portugal. This primary task, that involves systematizing inventory rules and implementing a methodical and updated inventory of cultural heritage, is an essential tool for managing and safeguarding this heritage. The inventory of urban heritage, comprising archaeological and architectural heritage, is particularly complex as it is intertwined with land use management.